Communities, households and animals - Marciniak, Arkadiusz (Documenta Praehistorica, 2008)
This paper intends to scrutinize striking similarities in cultural developments and social transformations in Neolithic communities in the North European Plain of Central Europe and Central Anatolia in the early phase of their development and in the following post-Eearly Neolithic period. They will be explored through evidence pertaining to architecture and the organization of space, alongside changes in settlement pattern, as well as animal bone assemblages and zoomorphic representations. Social changes, in particular a transition from communal arrangements of local groups in the Early Neolithic to autonomous household organization in the following period, will be debated.
Keywords: Severna Evropa; Anatolija; archaeology; arheologija; neolitik; naselja; družbeni razvoj; družbene spremembe; demografski razvoj; gospodinjstva